Poor Quality of Sleep and its Association with Increased Body Mass Index and Mood Disturbances in Young Adults - Rajasegaran Rajalakshmi; Reddy Srija; Mani Thenmozhi (Journal of Clinical and Diagnostic Research, 2018)
Introduction: The ill-health effects of inadequate sleep and sleep-related disorders are usually underestimated by the general population. Recent studies have reported a declining trend in the quality of sleep among young adults due to the extensive use of electronic media. However, data regarding the quality of sleep and its association with Body Mass Index (BMI) and psychological status of young adults is very limited. Aim: To assess the quality of sleep among young adults using simple self-reported pre-validated questionnaires and to measure the extent of its correlation with BMI and psychological status of the individuals. Materials and Methods: This cross sectional study was conducted between August 2016 and December 2016 in the Department of Physiology, Indira Gandhi Medical College and Research Institute, Puducherry, India. Four hundred young adults (20-23 years, both genders) were recruited in the study and their BMI was calculated using the Quetelet’s index. Quality of sleep, daytime sleepiness and symptoms pertaining to depression, anxiety and stress of the study participants were assessed using Pittsburgh Sleep Quality Index (PSQI) score, Epworth Sleepiness Scale score (ESS score) and Depression Anxiety Stress Scale Score (DASS score) respectively. The correlation between the study variables (PSQI scores, ESS scores, DASS scores, sleep hours and BMI) was determined using the Spearman correlation coefficient test. Results: Statistically significant positive correlation was observed between: a) PSQI scores and BMI (r=0.852, p<0.001); b) ESS scores and BMI (r=0.657, p<0.001); c) DASS scores and BMI (r=0.814, 0.929, 0.946 for Depression, Anxiety and Stress scores respectively, p<0.001); and d) PSQI scores and DASS scores (r=0.761, 0.838, 0.836 for Depression, Anxiety and Stress scores respectively, p<0.001). Duration of sleep hours showed a significant negative correlation with BMI (r=-0.533, p<0.001), PSQI scores (r=-0.714, p<0.001), ESS scores (r=-0.431, p<0.001) and DASS scores (r=-0.478, -0.532, -0.522 for Depression, Anxiety and Stress scores respectively, p<0.001). Conclusion: Poor quality of sleep predisposes to increased daytime sleepiness, increased BMIand mood changes in young adults.